2013
DOI: 10.1002/fam.2187
|View full text |Cite
|
Sign up to set email alerts
|

Two‐dimensional model of burning for pyrolyzable solids

Abstract: Quantitative understanding of the processes that take place inside a burning material is critical for the prediction of ignition and growth of fires. To improve this understanding and enable predictive modeling, we developed a numerical pyrolysis solver called ThermaKin. This solver computes transient rate of gaseous fuel production from fundamental physical and chemical properties of constituents of a pyrolyzing solid. It was successfully applied to the simulation of combustion of a broad range of materials. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 19 publications
0
39
0
Order By: Relevance
“…At 20 °C min -1 the ThermaKin pMLR values are higher than the experimental values and peaks are more defined. ThermaKin assumes that components are at equilibrium so discrepancies between the model and experimental data may arise when experimental conditions caused deviation from equilibrium [26]. …”
Section: Magnesium Acetatementioning
confidence: 99%
“…At 20 °C min -1 the ThermaKin pMLR values are higher than the experimental values and peaks are more defined. ThermaKin assumes that components are at equilibrium so discrepancies between the model and experimental data may arise when experimental conditions caused deviation from equilibrium [26]. …”
Section: Magnesium Acetatementioning
confidence: 99%
“…Lautenberger et al [12,13] have developed a generalized model, named "Gpyro", to simulate the fire behavior of non-charring polymers, other charring solids and intumescent coatings. Stoliarov et al [14][15][16] have also developed a model, named "ThermaKin", with a view to describing the pyrolysis of solid materials that were exposed to an external heat flux.…”
Section: Introductionmentioning
confidence: 99%
“…The selected reaction mechanism was solved using an in-house numerical pyrolysis code, ThermaKin [8,9], which was run in an infinitely fast transport mode (i.e., the solid was programmed to follow the heating rate set in the TGA experiment and all volatiles were instantaneously removed from the solid). The Arrhenius pre-exponential factor, activation energy, and product yields of each reaction were adjusted until a desirable agreement, measured by the coefficient of determination (R 2 ) and visual data comparison, with the experimental data was reached.…”
Section: Kinetics Of Thermal Decompositionmentioning
confidence: 99%
“…Unlike the previous manuscripts, the focus is not on technical details of particular procedures but rather on the overall workflow and reasoning behind selection of the key technical elements. It is also demonstrated that, despite some differences in the submodel formulations among modern pyrolysis codes [8][9][10][11], parameters obtained using one code can be utilized in another with a reasonable expectation for similar predictions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation